Use Of Extended Deep Inferior Epigastric Artery Flap In Management Of Groin Wounds With Exposed Vessels - Dr. Ramesh Kumar Sharma (Indian Journal of Plastic Surgery, 1992)
Consistency, safety, ease and least morbidity of donor site are some of the factors which have made extended inferior epigastric artery based flap popular. For major reconstruction in groin region where important structures are exposed, its use in demonstrated in eight cases.